The challenges of distance learning in countries undergoing transition during the COVID-19 pandemic - case study - Rugova, Naser; Nikci – Rexha, Elmire; Berisha, Elmi; Bajrami, Fallanza Beka (Technium Social Sciences Journal, 2021)
Virtual learning, also known as online learning or distance learning has transformed the face of the education system for quite some time. Now, it is rapidly becoming an integral aspect and a common tool, in the broader aspect of higher education, as a result of the COVID-19 pandemic. In addition to providing an alternative method of learning in the digital age, online learning offers students the opportunity to learn new skills or improve existing ones. On March 11, 2020, the World Health Organization declared COVID-19 a global pandemic. Following the speed with which COVID-19 spread to all parts of the world and to curb the spread of the disease, most governments around the world, including the Republic of Kosovo, authorized unprecedented social control measures to stop this disease unknown. These measures, among others, required social distancing and temporary physical closure of educational institutions. The first case of COVID 19 in Kosovo was identified on March 13, 2020, social distancing - full closure came into force on March 15, while UBT Higher Education Institution started online learning on March 16, 2020, the first in Kosovo and possibly in the Western Balkans. This teaching-learning process was a novelty for Kosovo and was applied for the first time. Objective: The main objective of the current survey was to study the impact of E-learning on students’ academic performance and their evaluations of this form of teaching in general. The purpose of this paper is to reflect as professionally as possible the organization of distance learning, the effects on the teaching and learning process as well as the form and level of communication and teacher-student relations in this process which was a novelty for Kosovo and UBT as one of the largest Private Colleges in the region.